IMPLEMENTASI KEBIJAKAN PENATAAN DAN PEMERATAAN BERDASARKAN BEBAN KERJA GURU SMA NEGERI DI TEMBILAHAN KOTA KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Ere Mardella Arbiani; Azhar Azhar; Mahdum Mahdum (Universitas Riau, 2019)
This research was aimed at finding out the structuring and equality policies of the teaching loads of the state Senior High School (SMAN) teachers of Tembilahan Kota, Indragiri Hilir District. The data were gathered through observation, interview and documentation. The informants of the research were employees of the District Education Office, school supervisors, head teachers, and a number of teachers in the Sub-district of Tembilahan Kota. The data analysis used in this study was policy analysis since the research employed the qualitative approach. The findings of the research indicated that (1) the program planning of the structuring and equality of the teachers’ teaching loads has been implemented. (2) In its implementation, however, there were teachers who could not have 24 teaching hours in a week. (3) The implementation of the planned program of the structuring and the equality of the teachers’ teaching loads was running smoothly, but not yet as maximal as expected.